The Precision of Screening Questionnaires for Diabetes Mellitus Type 2 and Hypertension Compared with the Gold Standard in Primary Care - Seta Nurhayati Mularum; Hari Kusnanto; Wahyudi Istiono (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
Background: Diabetes mellitus (DM) and hypertension are health issues that are the focus of the Indonesian government, especially in the era of Universal Health Coverage/Jaminan Kesehatan Nasional (JKN). The prevalences have been steadily increasing daily. Special Region of Yogyakarta (DIY) has the highest prevalence of DM in Indonesia, while hypertension prevalence is 25.7% according to data from Riskesdas 2013. Complications from diabetes and hypertension lead to decreased quality of life and premature death, therefore it is necessary to have a better management strategy to reduce the risks. Nowadays, there are no diabetes and hypertension screening questionnaires which have been validated and implemented in the district of Bantul. Therefore, it is important to develop screening questionnaires for early detection of diabetes and hypertension as a tool for primary care physicians to perform tasks at the preventive level.Objective: This study aimed to measure the accuracy of screening questionnaires to detect diabetes mellitus and hypertension in primary care in Bantul DIY.Methods: This study used a cross-sectional method. The subjects of the study were a group of individuals aged 40-60 years in Bantul who met the criteria inclusion and the criteria exclusion. The study subjects were asked to complete the screening questionnaires of diabetes and hypertension. The results were then compared with the gold standard of fasting blood sugar and blood pressure check. The data were analyzed by using multivariate regression tests.Results: The results of multivariate analysis showed that the risk factors were a history of baby born weight ≥ 4 kg or gestational diabetes mellitus and the abdominal circumference was an independent risk factor for the incidence of diabetes in general population. Being a baby born with weight ≥ 4 kg and abdominal circumference had p = 0.001: RR 2.75 (CI 95%: 1.5 to 5.0) and p = 0.036: RR of 8.08 (CI 95%: 1.15 to 56.8), respectively. The risk factor of age was an independent risk factor for hypertension with p = 0.003: RR of 3.1 (CI 95%: 1.4 to 6.6).Conclusion: History of a baby born with weight ≥ 4 kg and abdominal circumference were appropriate for screening DM, meanwhile the age was appropriate for screening hypertension.